Pembelajaran Matematika Daring dan Tatap Muka: Bagaimana Pandangan Siswa? - Elni Putri; Rhomiy Handican (Griya Journal of Mathematics Education and Application, 2023)
Network utilization to support learning activities is one of the innovations that must be developed by educators as part of the current education system that places them as facilitators. This study aims to look at students' perceptions of face-to-face and online-based learning. This research is a descriptive qualitative research. This research is in the form of questionnaires taken from 35 people as samples. Based on the results, it is known that a student's perception is not the same about face-to-face and online learning, where 82.9% feel it is easier to understand mathematics material when learning face-to-face while the rest choose online learning, so 77.1% of students consider that teachers, students and classmates have low interaction. In addition, 88.6% of students find it easier to develop social skills when learning face-to-face than online. 85.7% of students still need the teacher's role in person as a result of not maximizing online learning (60%). On the other hand, 60% of students find it easy to concentrate when learning online. Another view is that 68.6% of students think online learning is not more effective than face-to-face learning. The data exposure identifies that students' views prefer face-to-face learning compared to online, this implies that it is important for educators to offer a balanced choice between the two learning methods, paying attention to individual needs and students' learning styles.